Perfume Sales Application using the Economic Order Quantity (EOQ) Method - Syafriani, Dini; Suendri, Suendri (Sistemasi: Jurnal Sistem Informasi, 2024)
Computer systems are currently needed by many companies. The stock of goods owned by the company also needs to be considered. Maju Jaya Parfum in its sales can be higher or lower depending on the request of each seller, as a result, several difficulties and errors arise in recording reports on purchases and inventory of goods. Therefore, inventory management is very necessary to avoid circumstances that are detrimental to the company which can cause considerable expenses for the company. System development in this study uses the Waterfall model and the research method used is the R&D method, then the algorithm used is Economic Order Quantity (EOQ). The results showed that the existence of this system can display the ordering process, transactions of incoming goods and outgoing goods digitally instead of manually and be able to help Maju jaya perfume in overcoming the amount of perfume stock needed to be more effective and efficient.